Incidence and prevalence of vitreomacular traction with and without macular hole in Germany - Menzler J (Dove Medical Press, 2019)
Jacob Menzler,1 Aljoscha Steffen Neubauer,1,2 Christos Haritoglou,3 Timothy L Jackson4 1Institute for Health- and Pharmacoeconomics/Neubauer Consult, Munich, Germany; 2Private practice, Munich, Germany; 3Herzog Carl Theodor Eye Hospital, Munich, Germany; 4Department of Ophthalmology, Faculty of Life Course Sciences and Medicine, King’s College London, London, UK Purpose: Symptomatic vitreomacular adhesion (sVMA) comprises vitreomacular traction (VMT) and stage 1 and 2 full-thickness macular holes (MHs) associated with vitreomacular adhesion (VMA). We aimed to estimate the incidence and prevalence of sVMA in Germany.Materials and methods: A systematic literature review was conducted to identify the incidence and prevalence of sVMA based on international epidemiologic studies, weighted for study size and then averaged across eligible studies. A second systematic review aimed to estimate the proportion of vitrectomy undertaken for sVMA in Germany. This was combined with the reported number of vitrectomies in Germany in 2016 to estimate the number of patients undergoing vitrectomy for sVMA.Results: The prevalence of sVMA is 1,365 per 100,000 population, with an incidence of 6.96 per 100,000 per year. For Germany, this translates to 1,119,300 cases, with 5,700 new cases reported annually. Analyzing the national hospital statistics, ~2,300 patients undergo vitrectomy due to sVMA in Germany each year, of which about 1,700 patients have VMT.Conclusion: Incidence figures, driven by patients presenting to clinic, are much lower than expected based on population-based studies, suggesting that many patients with sVMA exist outside of the clinic system. Keywords: epidemiology, vitreous body, vitreous pathology, vitreous adhesion, vitreous detachment, pars plana vitrectomy